2007
DOI: 10.1038/sj.bjc.6604044
|View full text |Cite
|
Sign up to set email alerts
|

Expression of N-acetylglucosaminyltransferase V in endometrial cancer correlates with poor prognosis

Abstract: N-acetylglucosaminyltransferase V (GnT-V) is an enzyme that catalyses b1 -6 branching of N-acetylglucosamine on asparagine-linked oligosaccharides of cell proteins. The present study aimed to investigate GnT-V expression and its prognostic significance in endometrial cancer. N-acetylglucosaminyltransferase V expression was studied by immunohistochemistry in 74 surgically resected endometrial cancers, and the staining intensity was evaluated. High GnT-V expression in tumour cells was found in 43 (58.1%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…GnT-V expression is associated with a poor prognosis in breast cancer (37), colon cancer (14), and endometrial cancer (38). Consistent with these studies, we found that GnT-V was up-regulated in some cases of poorly differentiated invasive squamous skin carcinoma 4 .…”
Section: Discussionsupporting
confidence: 79%
“…GnT-V expression is associated with a poor prognosis in breast cancer (37), colon cancer (14), and endometrial cancer (38). Consistent with these studies, we found that GnT-V was up-regulated in some cases of poorly differentiated invasive squamous skin carcinoma 4 .…”
Section: Discussionsupporting
confidence: 79%
“…Western blot analysis for GnT-IVa protein was performed as previously described (Yamamoto et al , 2007), with an anti-GnT-IVa mAb (M-71; Santa Cruz Biotechnology) diluted 1 : 1000. Immunoreactive proteins were stained using a chemiluminescence detection system (ECL; Amersham, Arlington Heights, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation was performed using 1.5 mg of protein that was extracted from cells with an anti-human β hCG mAb (HCG-60; Santa Cruz Biotechnology) or β 1 integrin mAb (BV7; Abcam, Cambridge, UK), as previously described (Yamamoto et al , 2007). The anti- β hCG mAb and anti- β 1 integrin mAb (MAB2247; Chemicon International, Temecula, CA, USA) were used at a dilution of 1 : 200 and 1 : 1000, respectively, and western blotting and DSA lectin blotting were performed using the above protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of these oligosaccharides on several human tumors such as those of breast, colon, esophagus, endometrium and gliomas have been shown to be associated with the metastatic phenotype [9][10][11] . Their expression on several human and murine cancer cell lines has been shown to correlate with the metastatic potential [9].…”
Section: Introductionmentioning
confidence: 99%